Ligilactobacillus salivarius CNCM I-4866, a potential probiotic candidate, shows anti-inflammatory properties in vitro and in vivo - Carbonne, Celia; Chadi, Sead; Kropp, Camille; Molimard, Lise; Chain, Florian; Langella, Philippe; Martin, Rebeca (Frontiers in Microbiology, 2023)
Introduction The aim of this work was to characterize a new strain of Ligilactobacillus salivarius (CNCM I-4866) (CNCM I-4866) to address its potential as probiotic with a special focus on intestinal inflammation. Potential anti-inflammatory abilities of this strain were evaluated through in vivo and in vitro experiments. Methods Firstly, the strain was tested in a murine acute inflammation colitis model induced by DNBS. In vitro characterization was then performed with diverse tests: modulation capability of intestinal permeability; study of the impact on immunity profile through cytokines dosage; capacity to inhibit pathogens and adhere to intestinal cells lines. Production of metabolites, antibiotic resistance and survival to gastro-intestinal tract conditions were also tested. Results In vitro assay has shown a reduction of colonic damage and markers of inflammation after treatment with CNCM I-4866. Transcriptomic analysis performed on colons showed the capacity of the strain to down-regulate pro-inflammatory cytokines. L. salivarius CNCM I-4866 exerted anti-inflammatory profile by reducing IL-8 production by TNF-α stimulated cell and modulated cytokines profile on peripheral blood mononuclear cells (PBMC). It protected intestinal integrity by increasing trans-epithelial electrical resistance (TEER) on Caco-2 TNF-α inflamed cells. Additionally, L. salivarius CNCM I-4866 displayed inhibition capacity on several intestinal pathogens and adhered to eukaryotic cells. Regarding safety and technical concerns, CNCM I-4866 was highly resistant to 0.3% of bile salts and produced mainly L-lactate. Finally, strain genomic characterization allowed us to confirm safety aspect of our strain, with no antibiotic gene resistance found. Discussion Taken together, these results indicate that L. salivarius CNCM I-4866 could be a good probiotic candidate for intestinal inflammation, especially with its steady anti-inflammatory profile.